HOST IMMUNE PROFILING IN PATIENTS WITH SEVERE COVID-19: BIOMARKERS OF IMMUNE DYSREGULATION - Hasan, Husam Fadhil; Dahdoh, Mojtaba Qati; Ali, Hayder Mohsin (PT. Antis International Publisher, 2025)
Objective: Host immune profiling in severe cases of COVID-19 is an important area of focus that seeks to explain the immune dysregulation mechanisms impacting upon health. This study examines the immune landscape of patients suffering from severe COVID-19 in detail, mapping specific biomarkers of immune dysfunction. Method: By harnessing advanced technologies, including flow cytometry and transcriptomic analysis, this study captures the dynamic changes within immune cell subsets and their related pathways. Central to this exploration is understanding the interplay between innate and adaptive immunity in the context of severe COVID-19 infections. Results: Through comprehensive analysis, the study delineates the aberrant immune responses infiltrated by SARS-CoV-2, characterized by hyper inflammation, cytokine storm phenomena, and substantial variations in immunological profiles. Detailed profiling reveals notable deviations in neutrophil counts, lymphopenia, and altered cytokine levels. These disruptions are instrumental in the cascading complexities observed during disease progression. Consequently, the research identifies potential targets for modulation and future clinical application, thus aiming to enhance recovery rates and curtail mortality linked to severe COVID-19. Novelty: The identification of unique biomarkers offers profound insights into pathogenic processes, presenting opportunities for targeted therapeutic interventions and improved prognostic evaluations. The research posits that a strategic approach toward host immune profiling can profoundly impact the management and understanding of COVID-19. The findings underscore the necessity for precision medicine tailored to inherent immune irregularities, advocating for the integration of identified biomarkers in clinical practices to mitigate severe disease outcomes. The study contributes to existing literature by advocating for a paradigm shift, where immune profiling informs the design of bespoke therapeutic strategies and paves the way for innovative research trajectories in combating pandemic-related challenges.